Consuming artificial sweeteners may alter the structure and function of duodenal microbial communities - Ava Hosseini; Gillian M. Barlow; Gabriela Leite; Mohamad Rashid; Gonzalo Parodi; Jiajing Wang; Walter Morales; Stacy Weitsman; Ali Rezaie; Mark Pimentel; Ruchi Mathur (iScience, 2023)
Summary: Studies using stool samples suggest that non-sugar sweetener (NSS) consumption affects gut microbiome composition. However, stool does not represent the entire gut. We analyzed the duodenal luminal microbiome in subjects consuming non-aspartame non-sugar sweeteners (NANS, N = 35), aspartame only (ASP, N = 9), and controls (CON, N = 55) and the stool microbiome in a subset (N = 40). Duodenal alpha diversity was decreased in NANS vs. CON. Duodenal relative abundance (RA) of Escherichia, Klebsiella, and Salmonella (all phylum Proteobacteria) was lower in both NANS and ASP vs. CON, whereas stool RA of Escherichia, Klebsiella, and Salmonella was increased in both NANS and ASP vs. CON. Predicted duodenal microbial metabolic pathways altered in NANS vs. CON included polysaccharides biosynthesis and D-galactose degradation, whereas cylindrospermopsin biosynthesis was significantly enriched in ASP vs. CON. These findings suggest that consuming non-sugar sweeteners may significantly alter microbiome composition and function in the metabolically active small bowel, with different alterations seen in stool.